(untitled) (Research, Society and Development, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a topic that provokes great debate in the social and academic spheres, in addition to being considered a challenge for the areas of health and education. The objective of this work was to identify the epistemological aspects present in the different approaches to ADHD, through bibliographic research. Articles were searched on the following databases: CAPES Portal, Scielo and Google Scholar. The research was guided by the question: what are the epistemological motivations of the research expressed in the literature related to ADHD? Fifteen articles were selected, through a temporary cut of the last two five years. The study showed that research on ADHD presents some aspects that are contradictory, and it is important that the researcher knows or theoretical-methodological reference two authors and their position on the problem under study, with a view to directing influence it is not the result of your search.